1992
DOI: 10.1007/bf00013459
|View full text |Cite
|
Sign up to set email alerts
|

Control mechanisms of arctic lake ecosystems: a limnocorral experiment

Abstract: To assess the potential impact of human exploitation on arctic lakes and to determine how these ecosystems are regulated we initated a limnocorral experiment in Toolik Lake, Alaska, in the summer of 1983. The limnocorrals were 5 m in diameter and from 5-6 m in depth and were open to the sediments. In 1983 four limnocorrals were deployed in an isolated bay of Toolik Lake within a cross-classified treatment regime of high and low inorganic nitrogen and phosphorus additions and high and low free swimming fish add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 118 publications
0
17
0
Order By: Relevance
“…However, previous full-water fertilization experiments in Toolik Lake (Hobbie and Helfrich III, 1988;O'Brien et al, 1992;Hobbie et al, 1999) as well as Arctic ponds and streams (Douglas and Smol, 2000;Peterson et al, 1985) have revealed that microbial food webs of Arctic freshwaters respond in the same way as temperate lakes to P amendments; i.e., algal biomass increases dramatically, often paralleled by an increase in bacterial biomass. Still, the observed increases in bacterial biomass have mainly been interpreted as an indirect effect of stimulated primary production and associated input of organic C for subsequent bacterial utilization (Hobbie et al, 1999;O'Brien et al, 1992) rather than direct nutrient limitation of bacterial cells. The former interpretation is supported by a separate study where the direct effects of extraneous DOC on microbial food webs were studied in full-water Toolik Lake mesocosms (Hobbie et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous full-water fertilization experiments in Toolik Lake (Hobbie and Helfrich III, 1988;O'Brien et al, 1992;Hobbie et al, 1999) as well as Arctic ponds and streams (Douglas and Smol, 2000;Peterson et al, 1985) have revealed that microbial food webs of Arctic freshwaters respond in the same way as temperate lakes to P amendments; i.e., algal biomass increases dramatically, often paralleled by an increase in bacterial biomass. Still, the observed increases in bacterial biomass have mainly been interpreted as an indirect effect of stimulated primary production and associated input of organic C for subsequent bacterial utilization (Hobbie et al, 1999;O'Brien et al, 1992) rather than direct nutrient limitation of bacterial cells. The former interpretation is supported by a separate study where the direct effects of extraneous DOC on microbial food webs were studied in full-water Toolik Lake mesocosms (Hobbie et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This situation typically produces ultra-oligotrophic freshwater ecosystems due to low inputs of nutrients and organic carbon from terrestrial surroundings (Pienitz et al, 1997a, b). Low internal production is also a direct effect of annual temperatures that seldom exceed 5°C, but fertilization experiments have nevertheless shown that Arctic lakes can support high primary production in spite of the typically year-round low temperatures (O'Brien et al, 1992;Douglas and Smol, 2000). Another constraint on aquatic primary productivity in this region is the persistent ice cover that can cover lakes for more than 11 months per year.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies at the Arctic LTER site included fertilization and fish density manipulations of limnocorrals (O'Brien et al ., 1992) and fertilization of one-half of a naturally oligotrophic lake (Lake N-2) which had been divided by a plastic curtain and from which most fish had been removed (O'Brien et al ., in preparation) . The 'bottom-up' responses to fertilization included increases in nutrient pools and increased biomass of phytoplankton, nanoflagellates, benthic algae and submerged vegetation, benthic insects, and crustacean zooplankton (after a 1-2 year lag) .…”
Section: Discussionmentioning
confidence: 99%
“…The 'bottom-up' responses to fertilization included increases in nutrient pools and increased biomass of phytoplankton, nanoflagellates, benthic algae and submerged vegetation, benthic insects, and crustacean zooplankton (after a 1-2 year lag) . There was also evidence of top-down regulation, manifested in apparent selection favoring small zooplankton when fish were present (O'Brien et al, 1992) . Microplankton were not studied in either the limnocorrals or in lake N-2 prior to 1989 (the 3rd year offertilization of N-2) .…”
Section: Discussionmentioning
confidence: 99%
“…McNaughton 1989) and lakes (e.g. Arditi et al 1991;Hansson 1992;O'Brien et al 1992;Persson et al 1992), comparing trophic structure and/ or trophic level biomass across natural gradients of productivity (e.g. Hansson 1992;Persson et al 1992) or measuring the response of a community to nutrient enrichment (e.g.…”
Section: Introductionmentioning
confidence: 99%